Analisis Kemampuan Membaca Permulaan Selama Pembelajaran Daring Pada Peserta Didik Kelas 2 - Endang Purwati; Dedi Romli Triputra; Didik Tri Setiyoko (Peneliti.net, 2022)
This study aims to determine the initial reading ability during online learning in grade 2 students. This study uses qualitative research with data collection techniques using interviews, observation and documentation. The validity of the data is done by triangulation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. Based on the results of the study, it was concluded that the initial reading ability during online learning, the Covid-19 pandemic, students had a decline in learning, students had to face the online learning process (On the Network). Schools have a solution by implementing a combination of offline and online learning to make it easier for students to learn. The implementation of early reading skills activities during online learning at SD Negeri Sidamulya 01, the teacher sends materials about beginning reading. Students can mention the letters of the alphabet from A to Z, read and connect words and sentences, then recite in the form of videos sent via Whatsapp Groups or Video Calls and students can take direct reading tests with class teachers. For factors that hinder the ability to read early during online learning, lack of teacher guidance, internet access is not smooth, do not have a device (mobile phone), lack of parental assistance.